Circular bioeconomy-driven carotenoid production by Agrococcus sp. NP24 using cheese whey byproduct: process optimization and bioactivity assessment - Noby, Nehad; Elsayed, Fatma; Agami, Mahmoud M.; Soliman, Nadia A. (Frontiers in Microbiology, 2026)
Growing interest in the circular economy has promoted the use of agri-food wastes as fermentable and readily available substrates for microbial cultivation, offering a sustainable and cost-effective strategy for natural pigment production. In this study, cheese whey was utilized as a nutritional substrate for pigment synthesis by an isolated strain identified as Agrococcus sp. NP24 (PQ097720.1). The work further aimed to characterize the produced pigment and evaluate its bioactivity. The culture medium was optimized using a Box–Behnken design (BBD). The carotenoid profile of the extracted pigment was analyzed by HPLC-DAD and LC–MS. Pigment stability was assessed across a range of pH values and temperatures, and its antimicrobial, antioxidant, and anticancer activities were examined. The pigment was identified as zeaxanthin monoester (C14:0). The maximum pigment yield (0.0567 mg/mL extract) was achieved after 72 h at 20 °C using a medium containing 80% whey (v/v), 0.5% peptone (w/v), 0.97 g % casein (w/v), and supplemented with 0.5% (w/v) yeast extract and 0.5% (w/v) MgSO₄. The pigment remained fully stable up to 50 °C. Acidic conditions (pH 3–5) enhanced pigment absorbance compared to neutral and alkaline pHs. In contrast, exposure to daylight markedly reduced pigment stability, leaving only 26% residual activity after 1 h. The pigment exhibited potent antioxidant activity with an IC₅₀ of 6 μg/mL. It also showed cytotoxic and significant selectivity against the triple-negative breast cancer cell line MDA-MB-231 and the colorectal carcinoma cell line HCT-116, with IC₅₀ values of 3.3 mg/mL and 0.56 mg/mL, respectively, while no cytotoxicity was observed toward the HepG-2 hepatoblastoma cell line. The carotenoid did not display significant antimicrobial activity. In conclusion, the cost-effective production of NP24 carotenoids, combined with their favorable stability and bioactivity, supports their potential use as natural colorants in food applications.